Cardioprotective effects of the estrogen receptors modulators in the conditions of experimental acute myocardial infarction - Pavlov, S. V.; Levchenko, K. V.; Gorbachova, S. V. (Zaporozhye Medical Journal, 2017)
According to modern ideas, in myocardial infarction a cascade of pathobiochemical reactions is triggered directly in the ischemic focus, leading to a disturbance in the metabolism of cardiomyocytes, the launch of "parasitral" energy-producing reactions, the development of mitochondrial dysfunction, the complete blockade of the macroergic compounds synthesis, and as a result, cells death. In this regard, in the acute period of myocardial infarction it is pathogenetically justified to use drugs that can affect cardiomyocytes metabolism and restore the course of bioenergetic reactions in the cell. Aim of study – to evaluate the SERM cardioprotective effects in the conditions of acute myocardial infarction modelling with the use of the ST2 marker. Materials and methods: The experimental part of the work was performed on 120 mature rats - males weighing 190–230 grams. Small-focal acute myocardial infarction was modelled by the administration of coronary artery spasm induced agents – pituitrin and β1, 2, 3 isoprenaline adrenomimetic for 3 days. The investigated drugs tamoxifen citrate (0.1 mg/kg) (reg. № EF3300), toremifene (0.1 mg/kg) (reg. № 1705834), and also comparators – tiotriazoline (50 mg/kg) (UA/2931/01/02) and capicor (6 Mg/kg) (reg. № 11114) were injected intraperitoneally 20 minutes after the injection of isadrin for 3 days in the above stated doses. The myocardial infarction development was confirmed by electrocardiographic study, as well as the appearance of troponin I in blood plasma. The directivity and severity of pathobiochemical processes in the cardiac tissue, as well as the effect of the studied drugs on them, were studied through the enzyme-linked immunosorbent assay of nitrotirozine and homocysteine concentration in the heart homogenate and ST2 in blood plasma. Results: Systematic administration of a coronary artery spasm induced agents to laboratory animals led to a gradual, progressive ischemic lesion of cardiomyocytes. Biological markers of myocardial infarction Troponin, ST2 I were registered on the 3rd day after the administration of pituitrin and isadrin in the blood plasma of the control group. Using selective receptors modulators and reference preparations (thiotriazoline, capicor) in experimental therapy of rats with experimental myocardial infarction promoted the normalization of biochemical processes in cardiomyocytes. However, the effect of the studied drugs was unidirectional with various degree of intensity. All the drugs statistically significantly reduced oxidative stress marker products. The most marked effects were displayed by the selective estrogen receptors modulators toremifene and tamoxifen, which decreased in ST2 blood plasma level (by more than 46 %) providing realization of IL 33 cardioprotective properties. In addition, SERM can limit oxidative and nitrosyl stresses development, leading to a decrease in the concentration of homocysteine and nitrotirozine in the heart. Interaction of these effects of tamoxifen citrate in conditions of acute myocardial infarction modelling resulted in a marked cardioprotective effect, increasing the percentage of animals which survived to an average of 75 %. Conclusions. The cardioprotective effects of selective estrogen receptor modulators identified by us are an experimental foundation for the relevance and viability of further research in this direction.